Magic and Divination in the Old Testament. By Solomon Nigosian - Stökl, T. Jonathan (The journal of theological studies, 2010)
This slim volume contains an introduction and overview of magic and divination as they appear in the Hebrew Bible. Nigosian starts his book with a theoretical introduction to magic and divination, and then goes on with a description of several divinatory techniques, an overview of the various religious specialists related to divination and magic in the Hebrew Bible, and a short assessment on the biblical material. Nigosian, former professor of religious studies at Toronto University, approaches the subject with a deep knowledge both of the theory and of the biblical text.